Region Specific Up-Regulation of Oxytocin Receptors in the Opioid Oprm1−/− Mouse Model of Autism - Gigliucci, Valentina; Leonzino, Marianna; Busnelli, Marta; Luchetti, Alessandra; Palladino, Viola Stella; D’Amato, Francesca R.; Chini, Bice (Frontiers in Pediatrics, 2014)
Autism spectrum disorders (ASDs) are characterized by impaired communication, social impairments and restricted and repetitive behaviors and interests. Recently altered motivation and reward processes have been suggested to participate in the physiopathology of ASDs, and μ-opioid receptors (MORs) have been investigated in relation to social reward due to their involvement in the neural circuitry of reward. Mice lacking a functional MOR gene (Oprm1-/- mice) display abnormal social behavior and major autistic-like core symptoms, making them an animal model of autism. The oxytocin (OXT) system is a key regulator of social behavior and co-operates with the opioidergic system in the modulation of social behavior. To better understand the opioid-OXT interplay in the central nervous system, we first determined the expression of the oxytocin receptor (OXTR) in the brain of WT C57BL6/J mice by quantitative autoradiography; we then evaluated OXTR regional alterations in Oprm1-/- mice. Moreover, we tested these mice in a paradigm of social behavior, the male-female social interaction test, and analyzed the effects of acute intranasal OXT treatment on their performance. In autoradiography, Oprm1-/- mice selectively displayed increased OXTR expression in the Medial Anterior Olfactory Nucleus, the Central and Medial Amygdaloid nuclei and the Nucleus Accumbens. Our behavioral results confirmed that Oprm1-/- male mice displayed social impairments, as indicated by reduced ultrasonic calls, and that these were rescued by a single intranasal administration of OXT. Taken together, our results provide evidence of an interaction between OXT and opioids in socially relevant brain areas and in the modulation of social behavior. Moreover, they suggest that the oxytocinergic system may act as a compensative mechanism to bypass and/or restore alterations in circuits linked to impaired social behavior.